Acute ingestion of a meal rich in n-3 polyunsaturated fatty acids results in rapid gastric emptying in humans. - Robertson, MD; Jackson, K; Fielding, B; Morgan, L; Williams, C; Frayn, K (2002)
BACKGROUND: n-3 Polyunsaturated fatty acids (PUFAs) have proven benefits for both the development of atherosclerosis and inflammatory conditions. The effects on atherosclerosis may be partly mediated by the observed reduction in fasting and postprandial triacylglycerol concentrations after both acute and chronic n-3 PUFA ingestion. OBJECTIVE: The aim of this study was to assess gastric emptying and gastrointestinal hormone release after the consumption of mixed meals rich in n-3 PUFAs or other classes of fatty acids. DESIGN: Ten healthy women (aged 50-62 y) completed 4 separate study visits in a single-blind, randomized design. On each occasion, subjects consumed 40 g oil rich in either saturated fatty acids, monounsaturated fatty acids, n-6 PUFAs, or n-3 PUFAs as part of a mixed meal. [1-(13)C]Octanoic acid (100 mg) was added to each oil. Gastric emptying was assessed by a labeled octanoic acid breath test, and concentrations of gastrointestinal hormones and plasma lipids were measured. RESULTS: Recovery of (13)C in breath was enhanced after n-3 PUFA ingestion (P < 0.005). The cholecystokinin response after the n-3 PUFA meal was significantly delayed (P < 0.001), and the glucagon-like peptide 1 response was significantly reduced (P < 0.05). CONCLUSION: The inclusion of n-3 PUFAs in a meal alters the gastric emptying rate, potentially as the result of changes in the pattern of cholecystokinin and glucagon-like peptide 1 release.